Fostering a clean and sustainable environment through green product purchasing behavior: Insights from Malaysian consumers’ perspective - Al-Kumaim, Nabil Hasan; Al-Shami, Samer Ali Hussein; Muhamad, Salman Al Farisi; Hassan, Siti Hasnah; K. Alhazmi, Abdulsalam; Hishan, Sanil S.; Shabbir, Muhammad Salman; A. Gazem, Nadhmi; Mohammed, Fathey; Abu Al-Rejal, Hussein Mohammed (MDPI AG, 2021)
Rapid economic developments have led to the excessive consumption of environmental resources. Consumption patterns play a crucial role in deteriorating environmental conditions and influencing consumers to seek sustainability features while purchasing different products. The purpose of this paper was to analyze the sustainability factors that have prompted consumers in Malaysia to buy green products. The primary elements of this research focused on environmental concern, green product awareness, government support, perceived ecological value, community green practice, purchase intention, and green product purchase behavior. Additionally, to explain the relationship between the independent and dependent variables, this research employed the theory of planned behavior as a theoretical framework. A total of 300 questionnaires were collected and examined using smart PLS-SEM. The findings of the research suggest that all factors, including environmental concern, green product awareness, government support, perceived ecological value, community green practice, and purchase intention, influence consumers in Malaysia to purchase green products. Finally, this research discusses the contribution, limitations, and suggestions for future studies related to purchasing behavior towards green products.